“And to be malicious and belligerent / And not to lose feminine features”: Zuzanna Ginczanka’s Satirical World - Olech, Karolina (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The paper reflects on how Zuzanna Ginczanka, dubbed ‘Tuwim in a dress’ by Adam Ważyk, was finding her way – both as a woman and, above, as a poet – in the literary, cabaret world of Julian Tuwim, Jan Lechoń, or Antoni Słonimski. The paper focuses on the satirical output of the poet, which is why the author chose two works – namely Pochwała snobów (In Praise of Snobs) and Damskie kłopoty (Feminine Trouble) – as the basis for the analysis.